Rethinking Media and Communication : A Critical Sociological Lens - Allmer, Thomas,; Bilić, Paško, (Social Sciences E-Books Online, Collection 2026., 2026)
In this book, the authors address critical questions about the role of media and communication in capitalist societies. How do power structures shape communication processes? How are inequalities reinforced across different levels of society-micro, mezzo, and macro? Drawing on sociology, political economy, media studies and related fields, the book offers fresh insights into how communication supports capitalist domination, from media commodification to media concentration. It calls for a rethinking of how communication affects social relations and how social relations influence communication, exposing its deep connection to economic and political power. This book is essential for anyone seeking to understand the forces shaping today's media landscape.